Comparison of the Content Structures of Environmental Topics in Science Textbooks in Türkiye and Iran - Inaltekin, Tufan; Akcay, Hakan; Karaçöp, Ataman (Journal of Qualitative Research in Education, 2026)
The aim of this study was to compare the content structures related to environmental topics in primary and middle school science textbooks in Türkiye and Iran. A total of six textbooks from Türkiye and nine from Iran were analyzed as data sources. Conducted using document analysis, a qualitative research method the study revealed significant differences in how environmental topics are addressed in the textbooks of the two countries. It was found that the richness of content regarding environmental issues varies significantly between primary and middle school levels in both Turkish and Iranian textbooks. It was determined that science textbooks for primary and middle school in Türkiye offer much richer content compared to their Iranian counterparts in terms of data usage, content depth, scientific and technological perspectives, and the development of environmental awareness. Differences emerged between the two countries’ curriculum approaches regarding the effectiveness of environmental education. It was observed that science textbooks in Türkiye support a sustainability-based approach to environmental education to a greater extent than those in Iran. Although textbooks in both countries address many environmental topics, shortcomings were identified. A common shortcoming in both countries is the insufficient integration of the cultural context into environmental education. In this context, it is clear that environmental issues in the textbooks of both countries need to be addressed more comprehensively and evaluated from a global perspective. Furthermore, taking educational levels into account, the content should be structured in a more balanced and inclusive manner that reflects current conditions.